A Journey through Time and the European Visual Arts Based on the Novel Orlando, A Biography (A Perspective) - Carvalho, Cristina (VIA PANORAMICA: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2019)
The goal of this analysis is to establish a parallel between Virginia Woolf’s novel Orlando, A Biography, the 1992 film directed by Sally Potter, and a few examples of European canvases that may have inspired both artists. Woolf broke the shackles that still dominated British literature in the 1920s by writing a storyline that encompasses four centuries of a nation’s life and of mixed emotions for the novel’s leading character: Orlando was/is his/her name. Both the book published in 1928 and the film directed in 1992 start by presenting Orlando as an Elizabethan nobleman. As the plot unfolds, much like a caterpillar Orlando will evolve from a shy teenage boy into a confident adult woman. However, Woolf and Potter’s distinctive timelines and perceptions of the world explain the different paths offered by each author to Orlando in the last stages of their works. Focusing on this text’s purpose, its writer shall start by reflecting over some recurrent elements of the book written in 1928 as a means to praise the outstanding cultural background of Virginia Woolf at the time of its production. The following step will be to present canvases produced by painters like George Gower, Claude Monet, Gustav Klimt or even Marcel Duchamp that can be associated both to some excerpts of the novel and/or to scenes from the movie.